2014
DOI: 10.1002/joc.3931
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal patterns in the mean and extreme temperature indices of India, 1971–2005

Abstract: This study provides the comprehensive analysis of changes in mean and extreme temperature indices of India to assist the climate change mitigation and adaptation strategies and to add information for the global comparisons, using a high-resolution daily gridded temperature data set (1 • × 1 • ) during 1971-2005. In addition to the indices recommended by the World Meteorological Organization/CLIVAR Expert Team on Climate Change Detection and Indices, few more indices having social and agricultural implication a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 91 publications
5
41
0
2
Order By: Relevance
“…[14] demonstrated that within the process of warming, there is a larger rate of increase of minimum temperatures in relation to maximum temperatures, decreasing the values of temperature range [15]. Similar results were reported at different time scales.…”
Section: Introductionsupporting
confidence: 71%
“…[14] demonstrated that within the process of warming, there is a larger rate of increase of minimum temperatures in relation to maximum temperatures, decreasing the values of temperature range [15]. Similar results were reported at different time scales.…”
Section: Introductionsupporting
confidence: 71%
“…Most of the more than 1.25 billion people living on the Indian subcontinent are involved in outdoor activities, such as work in the agriculture and construction sectors [ Government of India , ]. As a result, heat waves are a major social and environmental concern [ Murari et al ., ; Panda et al ., ]. In particular, the rice‐wheat cropping system of north India, which ensures rural employment and the food security of the country, is at risk from heat waves and warm spells, observed in summer (March–May) and nonsummer months, respectively [ Krishna Kumar et al ., ; Lobell et al ., ; Teixeira et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Panda et al [17] examined trends in extreme indices of temperature over India using high resolution (1˝ˆ1˝) daily gridded data. Their studies indicate rises in hot extreme events (TXx, TX90p, TN90p, TNx, TR20, SU25 and WSDI) and decreases in cold extreme events (TX10p, TN10p, TXn, FD and CSDI) over most parts of the country for the period of 1970-2005.…”
Section: Annual Trends In Extreme Indices Of Temperature For 1970-2005mentioning
confidence: 99%
“…A number of studies on different spatial scales have been carried out over India for studying trends and variability in extreme indices of temperature [3,17,18] and precipitation [19][20][21]. However, the research work carried out on temperature and precipitation related extremes over the Himalayan region are very limited [22].…”
Section: Introductionmentioning
confidence: 99%